Dos becos e vielas ao paracampo : uma história da literatura marginal das periferias - Botton, André Natã Mello (2023)
The literary production of the Brazilian peripheries from the 2000s onwards challenges the structure of the hegemonic literary system. It is understood here as a cultural mark that pluralizes the contemporary Brazilian literary production, problematizing and challenging the hegemonic structures of the Brazilian literary field, of knowledge and power. The present research proposal reconstitutes, in the first part, the literary trajectories of Lima Barreto, Carolina Maria de Jesus, and João Antônio throughout the 20th century until the early 2000s. In the second part, the analysis is focused on Paulo Lins’ Cidade de Deus, Ferréz’ trajectory and the publication of three special editions of Caros Amigos magazine/Literatura Marginal - 2001, 2002, and 2004. The concept of paracampo is proposed since the collective organization of agents tensions the hegemonic literary field, interfering in the conditions and the form of production of culture from the Brazilian peripheries. This is the reason for the elaboration of the concept to interpret the specificities of the literary objects addressed and how the agents from the peripheries tension and interfere in the rules of art of the literary field. The paracampo, thus, is an intercultural epistemic proposal that should reflect the relations established among the agents that produce culture from the Brazilian peripheries and even beyond. In the last part, Sonia Regina Bischain and José Falero are brought to the discussion as examples of agents from the marginal literary paracampo of the peripheries